An IT-LSCD Model For IT Deprivation Among Low-Income Urban High School Students - Pickering-Reyna, Beverley (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study observed the Information Technology and Life Skills Career Development (IT-LSCD) model. IT-LSCD addressed three dilemmas urban high school students faced: 1) The digital divide, 2) Functional electronic illiteracy, and 3) Youth unemployment among underrepresented groups in a thriving technological society. The Information Technology 2000 Computer Training (IT 2000) Project utilized IT-LSCD to integrate technology literacy…